Triboelectric Nanogenerators as a Self‐Powered Motion Tracking System. (7th May 2014) - Chen, Mengxiao; Li, Xiaoyi; Lin, Long; Du, Weiming; Han, Xun; Zhu, Jing; Pan, Caofeng; Wang, Zhong Lin
<x xml:space="preserve">Abstract</x> Motion tracking is a key area of sensor systems for security, transportation, and high‐tech industry. In this work, a self‐powered motion tracking system is developed to monitor moving speed, direction, acceleration, starting and ending positions, and even the moving path of a moving object. Such a system is based on a set of triboelectric nanogenerators (TENGs) that are composed of two friction layers with opposite triboelectric polarities (Kapton and Aluminum) and operates in the sliding mode. Velocities of a moving object are monitored from −0.1 m s‐1 to +0.1 m s‐1 at a step of 0.01 m s‐1, and accelerations from −0.1 m s‐2 to +0.1 m s‐2 at a step of 0.02 m s‐2. Furthermore, an 8 × 8 two‐dimensional coordinates system with 16 groups of TENGs is created, and the moving path of an object is obtained. This study opens up a new area of TENGs as active sensors with great potential in self‐powered systems, positioning detecting, motion tracking, environmental and infrastructure monitoring, and security.